"الإحالة الإشارية في نصوص البخلاء للجاحظ" - يحيا مالك; الراهب سميرة; دندش سائر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول هذا البحث ظاهرةً لغويةً نصيّةً، هي الإحالة التي لم تأخذ نصيبها الكافي، ولم تحظَ باستقلال على الرغم من أهميتها في الدرس اللساني، فالإحالة بمفهومها العام يقصد بها وجود عناصر لغوية لا تكتفي بذاتها من حيث التأويل، ولا بدّ من العودة فيها إلى ما تشير إليه من أجل تأويلها، والإشارة إحدى أدوات هذه الإحالة، وقد خصصت بحثي هذا للحديث عنها لتبيين الأثر الذي تتركه الإحالة الإشارية في تحقيق الاختزال بتجنّب تكرار المشار إليه، وأثر ذلك في تحقيق التماسك والترابط بين أجزاء النص. واخترت كتاب البخلاء للجاحظ مجالاً للبحث؛ لأنه يتناول البخلاء في حيلهم وطبقاتهم وأجناسهم، فتوزّعت فيه الإحالات الإشارية داخل النسيج النصي للقصص والرسائل والنوادر، وهذا ما جعل نصوص البخلاء للجاحظ أكثر مناسبةً لدراسة التماسك النّصي. This research deals with a textual linguistic phenomenon, which is the referral that didn’t receive the appropriate appreciation and was never independent (despite its importance) in the lingual lesson. Referral in general is by meaning the existence of linguistic elements that are not independent when it comes to interpretation, and it must resort to what it indicates in order to interpret it. Indication is one of the tools of this referral, and we have dedicated our research to talk about it, to demonstrate the rule that this indicating reference played in accomplishing stenography by the avoidance of repeating what we are indicating, thus leading into coherence and contiguity between the parts of the text. And we have chosen al Jahez (al Bokhala) as a domain for our research, because its subject matter deals with stinginess and the stingy in all their tricks, classes, and genders, so that the indicating referrals have radiated throughout the fabric of the story and letters and drolleries, which made his text Al Bokhal more suitable for the study of the script coherence.